2016
DOI: 10.1007/s13201-016-0380-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of groundwater quality of Sabour block, Bhagalpur district (Bihar, India)

Abstract: This paper examines the quality of groundwater of Sabour block, Bhagalpur district of Bihar state, which lies on the southern region of Indo-Gangetic plains in India. Fifty-nine samples from different sources of water in the block have been collected to determine its suitability for drinking and irrigational purposes. From the samples electrical conductivity (EC), pH and concentrations of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Geographic information system (GIS) has been played a key role in the management of natural resources, and therefore, it may offer an appropriate method to integrate physicochemical data analyses of groundwater (El Omran et al 2014). However, the role of GIS in analyzing the spatial distribution of groundwater has been investigated by many authors (Verma et al 2016;Gorai and Kumar 2013;Srivastava et al 2012). In an earlier study, several models have been applied to estimate the hydrochemical distribution of water and soil (Nur et al 2012;Mosaferi et al 2014;Verma et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographic information system (GIS) has been played a key role in the management of natural resources, and therefore, it may offer an appropriate method to integrate physicochemical data analyses of groundwater (El Omran et al 2014). However, the role of GIS in analyzing the spatial distribution of groundwater has been investigated by many authors (Verma et al 2016;Gorai and Kumar 2013;Srivastava et al 2012). In an earlier study, several models have been applied to estimate the hydrochemical distribution of water and soil (Nur et al 2012;Mosaferi et al 2014;Verma et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of GIS in analyzing the spatial distribution of groundwater has been investigated by many authors (Verma et al 2016;Gorai and Kumar 2013;Srivastava et al 2012). In an earlier study, several models have been applied to estimate the hydrochemical distribution of water and soil (Nur et al 2012;Mosaferi et al 2014;Verma et al 2016). Geostatistics is a spatial statistical technique that can be used to assess and represent the distribution of concentration over space and time based on the relationship between sample points, and estimates the uncertainty of that prediction (Yeh et al 2009;Piccini et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Water scarcity and over-exploitation of groundwater resources are common in several parts of India (Garg and Hassan 2007;Tiwari et al 2009;Tiwari and Singh 2014). The principal cities and towns in India are facing serious problems related to groundwater-level depletion and groundwater quality deterioration (CGWB 2000(CGWB , 2001Gagan et al 2016;Gautam et al 2015;Krishan et al 2014;Raju et al 2011;Rodell et al 2009;Verma and Singh 2013;Verma et al 2016;Yadav et al 2012). The decreasing water level and the adverse impact of industrial and agricultural activities, mining, urbanization, and global climate change are increasing the pressure on groundwater resources.…”
Section: Introductionmentioning
confidence: 99%
“…This creates problem to groundwater with respect to its quality as well as quantity (Custodio et al 2016;Saravanakumar and Kumar 2011). Mining affects the physical and chemical changes in the mine environment resulting in groundwater pollution (Pathak and Banerjee 1992;Singh 1988;Verma et al 2017). Bukowski et al (2006) have reported that underground mining operations can be associated with many environmental effects like vulnerability of groundwater to pollution and the effects of mining on useful aquifers.…”
Section: Introductionmentioning
confidence: 99%